Single leg landing movement differences between male and female badminton players after overhead stroke in the backhand-side court - Zhao, X.; Gua, Y. (Human Movement Science, 2019)
Females showed higher anterior cruciate ligament (ACL) injuries rate on the opposite side of dominant hand compared with males during single leg landing in the backhand-side court after overhead stroke. The purpose of this study was to conduct biomechanics testing including kinematics and kinetics to provide some insights on the ACL injuries risks during single leg landing in the backhand-side court after overhead stroke between females and males. Twenty collegiate badminton players (10 females, 10 males) voluntarily participated in this study. Sagittal plane kinematic and kinetic data of the lower limb, and their ground reaction forces during the single leg landing in the backhand-side court after overhead stroke were collected. Results shown that, at the peak posterior ground reaction force (GRF) moment, the ankle dorsiflexion, knee and hip flexion angles of the female were lower than that of male. Meantime, the knee extension moment of the female was lower than that of males but the hip extension moment of the female was larger compared to males at the peak posterior GRF moment. The peak vertical and posterior GRF of female badminton players were larger than that of males. Decreased hip, knee, and ankle flexion angles at the peak posterior GRF moment and greater peak vertical and posterior GRF may expose female badminton players to the higher risk ACL injuries compared to males during single leg landing after overhead stroke in the backcourt-side. Preventative training programs designed to prevent the ACL injuries rate of female badminton players should take these factors into consideration.